A review on test procedure, energy efficiency standards and energy labels for room air conditioners and refrigerator-freezers - Mahlia, Teuku Meurah Indra; Saidur, Rahman (Elsevier, 2010)
Air conditioners and refrigerator-freezers aremajor energy users in a household environment and hence efficiency improvement of these appliances can be considered as an important step to reduce their energy consumption along with environmental pollution prevention. Energy efficiency standards and labels are commonly used tools to reduce the energy uses for household appliances for many countries around the world. The first step towards adopting energy efficiency standards is to establish a test procedure for rating and testing of an appliance. It may bementioned that an energy test procedure is the technical foundation for energy efficiency standards, energy labels, and other related programs. This paper reviews requirements and specifications of various international test standards for testing and rating of room air conditioners and refrigerators. A review on the development of the energy efficiency standards has been provided as well. Finally, energy labels that provide some useful information for identifying energy efficient products have been reviewed for these appliances. It may be stated that the reviewwill be useful for the developing countries who wish to develop these energy savings strategies. It is also expected to be useful to revise the existing strategies for a few selected countries who already implemented these strategies earlier.